Web-based GIS modelling of building-integrated solar photovoltaic system for the City of Cape Town - Adeleke, Adedayo Kelvin (School of Architecture, Planning and Geomatics, 2019)
Population increase in African cities have made it hard to reduce their ecological footprint and attain self-sustainability. This made the United Nations to put forward the seventeen sustainable development goals. Three of these goals centre on provision of clean energy and reduction of reliance on fossil fuels. It is therefore important for cities in Africa to chart a path of attaining sustainability. Consequently, the city of Cape Town is leading the drive for a greener city and self-sustainability in energy. Solar energy, which is regarded as a clean and renewable source of energy, makes it possible to generate electricity by using photovoltaics technology. However, the problem of creating awareness as to the potentials of building-integrated solar photovoltaic system persists. The study is aimed at using remote sensing and Geographic Information Systems (GIS) techniques in creating awareness about the potentials of building rooftops for solar photovoltaics installations in an urban setting. In achieving this, Light Detection and Ranging (LiDAR) data and aerial imagery are sourced from City of Cape Town municipality to serve as the primary data input. Four phases of analysis are involved: (1) extraction of whole building roof outline and its roof planes, using the integration of LiDAR-derived products and aerial imagery, in order to determine the surface area of the roof planes. This is achieved by developing a unique two-in-one, object-based classification rulesets; (2) estimating and validating the global solar radiation incidence on each roof plane, using a LiDAR-derived elevation model in a python script utilizing the GRASS script library; (3) evaluating the solar photovoltaic potential of each roof plane, using inputs from two previous phases to create a solar photovoltaic potential database; and (4) deploying the solution online to create awareness, by utilizing JavaScript and Hypertext Mark-up Language (HTML) to implement a map mashup, which incorporates tile map and table services. This results in a web-based solution, which can be queried to retrieve information about the solar photovoltaic potential of a building roof. From the results generated and the system developed, it becomes possible to remotely and sufficiently evaluate buildings in the city for solar photovoltaic potentials, designs and installations. Thereby reducing reliance on the fossil fuel generated electricity and improving the self-sustainability of the city.